Corn starch-based treatment improves rainwater quality - Nakada, Liane Yuri Kondo; Moruzzi, Rodrigo Braga [UNESP] (IWA Publishing, 2015)
Rainwater harvesting can provide an alternative water source, which may demand little treatment, depending on the end use. Some starches have been used in water treatment as coagulant/ flocculant/filtration aid, and might be applied as primary coagulant. Here, we show direct filtration with hydraulic rapid mixing, using 2-6 mg L-1 cationic corn starch as primary coagulant, considerably improves roof-harvested rainwater quality, achieving removal efficiencies of up to 71.7% of apparent colour, 78% of turbidity, 1.1 log-unit of total coliform, and 1.6 log-unit of Escherichia coli, meeting guidelines for turbidity, even for potable purposes. Cationic corn starch has proved to be a suitable primary coagulant when filtration is performed in a single-layer sand filter (coefficient of uniformity: 1.8, effective particle size: 0.52 mm), at hydraulic loading rate of 450 m day-1. However, a disinfection unit is required to meet an absence of faecal coliform.
Keywords: Corn starch; Direct filtration; Full-scale rainwater treatment; Rainwater harvesting